Islamic Social Finance and MSME Performance: A Moderated-Mediation Analysis across Aceh and North Sumatera - Firdaus, Rayyan; Soemitra, Andri; Marliyah, Marliyah (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are vital to Indonesia’s economy but continue to face barriers in financing, mentorship, and managerial capacity. Islamic Social Finance (ISF), implemented through Micro Waqf Banks (BWM), offers an inclusive solution by integrating joint liability schemes, mentoring, and capital assistance. While prior research affirms the role of ISF in enhancing access to finance and entrepreneurial growth, comparative evidence across regions with differing socio-cultural contexts remains limited. This study examines the differential effects of mentoring, joint liability, and capital provision on micro-entrepreneurial success in Aceh and North Sumatera. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (MGA) on responses from 350 micro-entrepreneurs, the results reveal that joint liability consistently supports enterprise performance, mentoring is more effective in Aceh, and capital provision is most beneficial in less developed areas. The findings indicate that local culture and institutional strength moderate ISF outcomes. Therefore, ISF programs should integrate standardized financial instruments with context-sensitive non-financial interventions to maximize their empowerment potential. This study contributes to the ISF literature and offers practical insights for designing regionally adaptive MSME empowerment policies. Abstrak Keuangan Sosial Islam dan Kinerja UMKM: Analisis Moderasi–Mediasi di Aceh dan Sumatera Utara. Usaha Mikro, Kecil, dan Menengah (UMKM) berperan penting dalam perekonomian Indonesia, namun masih menghadapi kendala akses pembiayaan, pendampingan, dan peningkatan kapasitas manajerial. Keuangan Sosial Islam (Islamic Social Finance/ISF) melalui Bank Wakaf Mikro (BWM) menjadi alternatif inklusif dengan menggabungkan skema tanggung renteng, pendampingan, dan bantuan modal. Meskipun ISF terbukti meningkatkan akses permodalan dan kinerja usaha, bukti komparatif lintas wilayah dengan karakter sosial berbeda masih terbatas. Studi ini meneliti pengaruh pendampingan, tanggung renteng, dan bantuan modal terhadap keberhasilan usaha mikro di Aceh dan Sumatera Utara menggunakan metode Partial Least Squares Structural Equation Modeling (PLS-SEM) dan Multi-Group Analysis (MGA) terhadap 350 responden. Hasil menunjukkan bahwa tanggung renteng berpengaruh positif di kedua provinsi, pendampingan lebih efektif di Aceh, dan bantuan modal lebih bermanfaat di daerah dengan keterbatasan ekonomi. Temuan ini menegaskan bahwa budaya lokal dan kekuatan kelembagaan memoderasi hasil ISF. Oleh karena itu, program ISF perlu mengombinasikan instrumen keuangan baku dengan dukungan non-keuangan yang peka terhadap konteks lokal untuk meningkatkan efektivitas pemberdayaan. Studi ini memperkaya literatur ISF dan memberikan rekomendasi kebijakan bagi strategi pemberdayaan UMKM yang adaptif wilayah.